SIMULASI PENGARUH LUAS PERMUKAAN ELEKTRODA TERHADAP TEGANGAN DAN KONSENTRASI PERMUKAAN ELEKTRODA PADA LEAD ACID REDOX FLOW BATTERY - Muhammad Ghufron; Silvi Hadila; Ervinka Felindia; Nikita Syaharani; Satria Pamungkas Panji Kumara; Irvan Fajar Hidayah; Gancang Saroja; Kurriawan Budi Pranata (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
Energy storage systems (ESS) with large storage capabilities, easy made, and low cost are in high demand. Dynamic lead acid battery (DLAB) as a breakthrough design compared conventional lead acid batteries offers a solution to these problems. Two Dimensional (2D) DLAB simulations with surface area variations of 8 cm2, 12 cm2, 16 cm2 and 20 cm2 were successfully build using the principle of tertiary current distribution and Nerst-Planck Interface. The results for one cycle charge-discharge test showed that the increase in surface area succeeded in increasing the final charging voltage with a value of 2.16 V; 2, 21 V; 2.30 V and 2.32 V and increase the initial discharging voltage by a value of 1.58 V; 1.59 V; 1.60 V and 1.62 V respectively but did not affect the electrode surface concentration. Dynamic lead acid battery has high energy efficiency of 70.6% -71.5%.